2021
DOI: 10.1111/ans.16886
|View full text |Cite
|
Sign up to set email alerts
|

Variation in treatment and outcomes for patients with chronic limb‐threatening ischaemia in New South Wales, Australia

Abstract: Background Chronic limb‐threatening ischaemia (CLTI) carries significant amputation and mortality risks. Australian population‐based outcomes for CLTI are inadequately known. This study aimed to distinguish factors associated with outcomes in the first 2 years after CLTI surgery. Methods By linking routinely collected health administrative and mortality data from New South Wales, this population‐based cohort study identified patients with ischaemic rest pain, gangrene or ulceration undergoing vascular surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…This The outcomes examined in these metrics of advanced presentation for PAD have a significant impact on patient quality of life. In Australia, emergency admissions with PAD have worse post-operative outcomes [23]. Most amputations for PAD are preceded by foot ulceration [24], and lower limb amputations are associated with significantly decreased quality of life, increased morbidity, mortality, and healthcare costs [25].…”
Section: Discussionmentioning
confidence: 99%
“…This The outcomes examined in these metrics of advanced presentation for PAD have a significant impact on patient quality of life. In Australia, emergency admissions with PAD have worse post-operative outcomes [23]. Most amputations for PAD are preceded by foot ulceration [24], and lower limb amputations are associated with significantly decreased quality of life, increased morbidity, mortality, and healthcare costs [25].…”
Section: Discussionmentioning
confidence: 99%
“…Despite more options for revascularisation, amputation for CLTI is increasing, with a recent review reporting 15%-20% of patients undergo amputation within 1 year of the onset of CLTI (Duff et al, 2019). In a large Australian population-based cohort study of CLTI outcomes 2 years after non-major amputation surgery (open or endovascular revascularisation, debridement or minor amputation), morbidity and mortality were significant, reporting 28.3% for CLTI mortality, 32.8% for perioperative complications, 47% for reoperation and subsequent major amputations at 3.6% (Choy et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Despite more options for revascularisation, amputation for CLTI is increasing, with a recent review reporting 15%–20% of patients undergo amputation within 1 year of the onset of CLTI (Duff et al, 2019). In a large Australian population‐based cohort study of CLTI outcomes 2 years after non‐major amputation surgery (open or endovascular revascularisation, debridement or minor amputation), morbidity and mortality were significant, reporting 28.3% for CLTI mortality, 32.8% for perioperative complications, 47% for reoperation and subsequent major amputations at 3.6% (Choy et al, 2021). For Australians with CLTI proceeding to amputation, the scope of post‐amputation problems in a case series review found in‐hospital mortality of 12%, severe morbidity of 76% and 54% of live separations requiring institutional care on a permanent basis following amputation despite an average length of stay of 35.1 days (Monaro et al, 2017).…”
Section: Introductionmentioning
confidence: 99%